Single-transistor organic electrochemical neurons - Junpeng Ji; Dace Gao; Han-Yan Wu; Miao Xiong; Nevena Stajkovic; Claudia Latte Bovio; Chi-Yuan Yang; Francesca Santoro; Deyu Tu; Simone Fabiano (Nature Communications)
Abstract Neuromorphic devices that mimic the energy-efficient sensing and processing capabilities of biological neurons hold significant promise for developing bioelectronic systems capable of precise sensing and adaptive stimulus-response. However, current silicon-based technologies lack biocompatibility and rely on operational principles that differ from those of biological neurons. Organic electrochemical neurons (OECNs) address these shortcomings but typically require multiple components, limiting their integration density and scalability. Here, we report a single-transistor OECN (1T–OECN) that leverages the hysteretic switching of organic electrochemical memtransistors (OECmTs) based on poly(benzimidazobenzophenanthroline). By tuning the electrolyte and driving voltage, the OECmTs switch between high- and low-resistance states, enabling action potential generation, dynamic spiking, and logic operations within a single device with dimensions comparable to biological neurons. The compact 1T–OECN design (~180 µm2 footprint) supports high–density integration, achieving over 62,500 neurons/cm2 on flexible substrates. This advancement highlights the potential for scalable, bio-inspired neuromorphic computing and seamless integration with biological systems.